2010
DOI: 10.1155/2010/923193
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus multilocularisand Its Intermediate Host: A Model of Parasite-Host Interplay

Abstract: Host-parasite interactions in the E. multilocularis-intermediate host model depend on a subtle balance between cellular immunity, which is responsible for host's resistance towards the metacestode, the larval stage of the parasite, and tolerance induction and maintenance. The pathological features of alveolar echinococcosis. the disease caused by E. multilocularis, are related both to parasitic growth and to host's immune response, leading to fibrosis and necrosis, The disease spectrum is clearly dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
178
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(185 citation statements)
references
References 114 publications
(139 reference statements)
5
178
0
2
Order By: Relevance
“…Studies with resistant mouse models revealed that mice mount an early IFN-g response during trypanosoma infection followed by a late cytokine switch to the anti-inflammatory IL-10, . This remarkable cytokine shift was also described in helminths infection models such as S. mansoni and Echinococcus multilocularis, which rather protects the host from extensive tissue damage under unrestricted Th1-cell mediated inflammation [36]. As helminths are experts in modulating the immune system, their antigens are extensively studied to define how they trigger antigen-presenting cells such as macrophages and DCs to induce Th2-cell responses [19].…”
mentioning
confidence: 86%
“…Studies with resistant mouse models revealed that mice mount an early IFN-g response during trypanosoma infection followed by a late cytokine switch to the anti-inflammatory IL-10, . This remarkable cytokine shift was also described in helminths infection models such as S. mansoni and Echinococcus multilocularis, which rather protects the host from extensive tissue damage under unrestricted Th1-cell mediated inflammation [36]. As helminths are experts in modulating the immune system, their antigens are extensively studied to define how they trigger antigen-presenting cells such as macrophages and DCs to induce Th2-cell responses [19].…”
mentioning
confidence: 86%
“…None of those were located on Emcys1, implying that the host factors, apart from those expressed in the liver, may have more influence on the cyst establishment and that the earlier stages of infection such as hatching, activation, penetration, migration and predilection of oncospheres might be determinants of susceptibility to the infection. As recently reviewed by Vuitton and Gottstein (2010), the cell-mediated immune responses, especially acute inflammatory Th1 response, are known to play an important role in the early stage of E. multilocularis infection. Furthermore, early inflammation induced by complement activation was shown to be important in controlling the establishment of the metacestode of Echinococcus granulosus, a closely related parasite (Breijo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Последнее особенно важно, поскольку, как указано выше, при паразитарных заболеваниях многие паразиты выживают, благодаря наличию у них эволюционно выработанных механизмов защиты, являющихся следствием сближения структуры их белков с белками хозяина [21]. Именно это сближение структуры белков, которое произошло в результате параллельной эволюции паразита и хозяина, приводит к тому, что многие паразитарные белки не проявляют свои иммуногенные свойства в организме инвазированного хозяина, что создаёт трудности в иммунодиагностике и иммунопрофилактике гельминтозов и способствует существованию паразитов в организме хозяина довольно длительный период времени.…”
Section: результаты и обсуждениеunclassified